ASPECTS OF TERRITORIAL ORGANIZATION OF ECONOMY BUT INSTITUTIONAL PROVIDING IN MODERN TERMS - KHARCHENKO, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
A problematic trend is the orientation of the regional economy mainly to the raw materials sector, a decrease in the rate of introduction of innovative types of products, and low entrepreneurial activity of the population. The unproductiveness of the economy and the uneven distribution of it increase the asymmetry of interregional and subregional sustainable development. Trends towards increasing disparities are also observed in terms of the volume of industrial products sold, exports, attracting investments, the level of attracting capital investments per person, etc. The uneven level of development of the regions, which especially deepens at the level of cities, towns, and villages, leads to an imbalance of the territory of Ukraine, which threatens its integrity. The growth of territorial disparities in the level and quality of life of the population increases external and internal migration processes, which are practically uncontrollable, lead to the outflow of human resources, especially from border and rural areas, monofunctional cities, and disrupts the settlement system. As a result, there is a growing gap between the center and territories remote from it, loss of control over them, further aggravation of the crisis in underdeveloped territories and their marginalization. In the article the features of influence of territorial organization of economy are investigated and her institutional providing, possibility of creation of new and strengthening of existent methodological contradictions, враховуючі modern calls. It is indicated, priority directions of optimization of the інституціанального providing of territorial organization of economy. It is marked that in modern terms the key factors of territorial organization of economy in the countries-members of ЄС are confess innovative activity, capitalization of human potential and effective management. An author is indicate conceptual principles of optimization of the institutional providing of territorial organization of economy in modern terms
Keywords: institutional providing; territorial organization; economies; regional development; development of productive forces